2014
DOI: 10.1039/c3cp54556c
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of actinyl ions in water: a molecular dynamics simulation study

Abstract: The dynamics of actinyl ions (AnO2(n+)) in aqueous solutions is important not only for the design of advanced separation processes but also for understanding the fate of actinides in the environment. The hazardous nature of actinides makes it difficult to measure transport and thermodynamic properties experimentally, so predictive simulations are an attractive method for studying these systems. Here, we report the results of atomistic-level molecular dynamics simulations of actinyl ions (of U, Np, Pu, and Am) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
56
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 82 publications
(137 reference statements)
13
56
2
Order By: Relevance
“…The values of diffusion coefficients for bulk water, water in the U1 system, and uranium atom of uranyl ion in the U1 system are similar to those given by Tiwari et al for the TIP3P model of water. 24 The self-diffusion coefficients for uranyl ion were observed to be lower for SPC/E water as compared to those for TIP3P water. The diffusivity values obtained for water molecules and uranyl ions in aqueous uranyl solution with SPC/E water model are in good agreement with those obtained earlier using molecular dynamic simulations.…”
Section: Resultsmentioning
confidence: 96%
“…The values of diffusion coefficients for bulk water, water in the U1 system, and uranium atom of uranyl ion in the U1 system are similar to those given by Tiwari et al for the TIP3P model of water. 24 The self-diffusion coefficients for uranyl ion were observed to be lower for SPC/E water as compared to those for TIP3P water. The diffusivity values obtained for water molecules and uranyl ions in aqueous uranyl solution with SPC/E water model are in good agreement with those obtained earlier using molecular dynamic simulations.…”
Section: Resultsmentioning
confidence: 96%
“…In that way, the electrostatic interactions may affect the behaviour of the complex and may, for example, reduce the probability for the magnesium ion to associate with a second carboxylate ion, since it is screened with the most negative charge by the surrounding water molecules. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 In Table 3, the number of exchanges of water molecules [34][35][36][37][38] in the first solvation shell has been reported for separation distances from 2 Å to 6 Å. For the divalent ions, most exchanges are found for the bigger ions, Ba 2+ and Sr 2+ , compared with the small ones (Mg 2+ and Ca 2+ ).…”
Section: Fig 5: Helmholtz Free Energy E Int Curves Of the Metal Imentioning
confidence: 97%
“…Various DFT investigations of the aquo solvation structure of uranyl found a equatorial uranyl CN of 5, [91][92][93][94][95][96][97][98] with equatorial U-O bond lengths of 2.4 93,95 to 2.53 Å. 94,97 In general both AIMD [99][100][101] and MD 87,[102][103][104][105] simulations of the uranyl solvation environment indicated a coordination number of 5 and the U-O bond distance is identified as 2.36 102 to 2.48 Å. 104,105 The MD study by Rodríguez-Jeangros et al 106 identified an average CN of 4.39 as uranyl is equatorially coordinated by either 4 or 5 waters.…”
Section: +mentioning
confidence: 99%